Fatal Strongyloides Hyperinfection Complicating a Gram-Negative Sepsis after Allogeneic Stem Cell Transplantation: A Case Report and Review of the Literature - Isabel Izquierdo; Javier Briones; Rafael Lluch; Cristina Arqueros; Rodrigo Martino (Case Reports in Hematology)
Strongyloides stercoralis is an intestinal nematode that causes strongyloidiasis, which affects 30 to 100 million people worldwide. Risk factors for hyperinfection and disseminated disease include immunosuppressive drug therapy, human T-lymphotropic virus-1 (HTLV-1) infection, solid organ and bone marrow transplantation, hematologic malignant diseases, hypogammaglobulinemia, and severe malnutrition and associated conditions. The diagnosis can be difficult because a single stool examination fails to detect larvae in up to 70% of the cases, and the symptoms are nonspecific. Although eosinophilia is a common finding in patients with chronic Strongyloides infection, it is an unreliable predictor of hyperinfection. Furthermore, the lack of eosinophilia while receiving immunosuppressive therapy cannot reliably exclude the underlying chronic Strongyloides infection. We report here a fatal Strongyloides hyperinfection in a patient receiving allogeneic stem cell transplantation; risk factors and outcome in this clinical setting are discussed.